Legal Pluralism: Interactions Between Official and Unofficial Laws: The Case Study of a Multi-ethnic Community Farm - Gabriela Ribeiro Farinha (Oñati Socio-Legal Series, 2015)
A multi-ethnic community farm, located in California, was created in 2011 to be commonly exploited by refugees and emigrants from different countries. This paper aims to describe, as an observable fact, how distinct non-state normativities behave and relate in their dynamic process of interaction, surpassing the usual state/local law bases of analysis. The farm was approved by the state authorities and the NGO has created its regulations. Concomitantly, the distinct communities of farmers have defied and transformed the farm’s regulations by incorporating their competing legal land tenure regimes and legal postulates in the same structure of the unofficial law of the farm, through a common frame of meaning and the enactment of the “autonomy rule”. This has allowed the growers to follow their normativities inside the farm. However, its creation process and daily practice also exposes the relevance of the official law in its constitution, shape and function. En 2011 se creó en California una granja multiétnica comunal, para que fuera explotada en comunidad por refugiados y emigrantes de diferentes países. Este artículo pretende describir, como hecho observable, cómo se comportan y se relacionan normativas no estatales en un proceso dinámico de interacción, superando las bases de análisis estado/local habituales del derecho. Las autoridades estatales aprobaron la granja, y la ONG creó su propia normativa. Al mismo tiempo, las diferentes comunidades de agricultores han desafiado y transformado el reglamento de la granja, incorporando sus regímenes legales de tenencia de tierras vigentes, y los postulados legales en la misma estructura del derecho no oficial, a través de un marco común de significado y la promulgación de la “norma de autonomía”. Esto ha permitido a los productores seguir sus normativas dentro de la finca. Sin embargo, su proceso de creación y práctica diaria también pone de manifiesto la importancia del derecho oficial en su constitución, forma y función. DOWNLOAD THIS PAPER FROM SSRN: http://ssrn.com/abstract=2390129